Concurrent validity of the Polar Precision Prime® photoplethysmographic system to measure heart rate during a tennis training session - Ruiz-Malagón, E. J.; Castro-Infantes, S.; Ritaco-Real, M.; Soto-Hermoso, V. M. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2025)
Monitoring heart rates has always been important for coaches and athletes. Photoplet-ismographic systems (PPG) are supposed to be less capable of determining heart rate measure in activities with high upper limb movement, such as tennis. Thus, the aim of this study was to determine the concurrent validity of the Polar Precision Prime® (PPP®) system existing in the Polar Ignite® sports watch. This was accomplished by measuring averaged heart rates during a tennis training session, divided in three parts (warm-up, main-part and cool-down) and averaged per 10 s intervals by comparing data with the Polar H-10® chest strap synchronised with the Polar V800® (criterion measure). A group of 40 tennis players (32 males, 8 females) took part in the study. Mean average values and between-systems differences and Mean Absolute Percentage Error (MAPE) were obtained (<4.04 bpm; <5.03%), reporting small differences in all session parts and 10 s intervals. The PPP® system reported high correlation (r > 0.89) and excellent ICC (ICC > 0.96) in all session parts except the 10 s intervals where the ICC were good (0.85). The systematic bias and random error during the warm-up and 10 s intervals were greater (-0.99 ± 6.02 bpm and -2.41 ± 5.86 bpm, respectively) than the main-part and cool-down (-0.51 ± 1.16 bpm and -0.44 ± 4.02 bpm, respectively). Results suggest that the PPP® system precision is not altered despite upper limb movements during 1-h tennis training sessions. In conclusion, the Polar Ignite® PPG system is a valid tool for monitoring heart rate during a tennis training session.